Climate Change: International Law and Global Governance 2013
DOI: 10.5771/9783845242774-877
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Solutions in the Context of Climate-Change-Related Loss and Damage: Needs, Gaps and Roles of the UNFCCC in Addressing Loss and Damage

Abstract: The UNFCCC can foster long-term commitment to risk transfer in order to enable sustainable solutions and partnerships. A global approach to risk transfer, embedded in a coherent strategy to manage the negative impacts of climate change, can be a sustainable solution to parts of the loss and damage spectrum. An international climate-risk insurance facility will help better diversify risks of loss and damage from extreme weather events, lower the costs of managing these risks, and ensure more timely and targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Weather-related events are reported to have been increasing in the past three decades (Warner et al, 2012). The Intergovernmental Panel on Climate Change (IPCC) has concluded that current climate change effects have changed the frequency, intensity and duration of extreme weather and climate events (Seneviratne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Weather-related events are reported to have been increasing in the past three decades (Warner et al, 2012). The Intergovernmental Panel on Climate Change (IPCC) has concluded that current climate change effects have changed the frequency, intensity and duration of extreme weather and climate events (Seneviratne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%